Excitation of elliptical and toroidal Alfvén eigenmodes by 3He-ions of the MeV-energy range in hydrogen-rich JET plasmas. (25th August 2020) - Kiptily, V.G.; Kazakov, Ye.; Fitzgerald, M.; Nocente, M.; Iliasova, M.; Khilkevich, E.; Mantsinen, M.J.; Nave, M.F.F.; Ongena, J.; Sharapov, S.E.; Shevelev, A.E.; Štancar, Ž.; et al.
Abstract: Elliptical (EAE) and toroidal Alfvén eigenmode (TAE) instabilities have been observed in hydrogen-rich JET discharges of the D- ( 3 He) -H ion cyclotron resonance heating (ICRH) scenario, which is characterized by strong absorption of radio frequency waves at very low concentrations of the resonant 3 He-ions. In the experiments, core localized TAEs with a frequency f TAE ≍ 280 kHz with mode numbers n = 3, 4, 5 and 6 were detected. Following the phase with TAE excitation, EAE modes at higher frequencies f EAE ≍ 550–580 kHz with mode numbers n = 1, 3, 5 were seen. These high frequency modes indicate that a MeV range population of trapped energetic ions was present in the plasma. The experimental evidence of existence of the MeV-energy 3 He-ions able to excite the AEs is provided by neutron and gamma-ray diagnostics as well as fast ion loss measurements. The ICRH modelling code calculations confirm the acceleration of 3 He-ions to MeV energies. The magnetohydrodynamic (MHD) analysis results are consistent with the experimental data showing that the MeV 3 He ions satisfy to resonant conditions interacting with TAE and EAE modes. This experiment demonstrates the efficient plasma heating mimicking the conditions representative for the ITER plasmas and contribute to the understanding of fast-ion interaction with MHD wave modes.